The Immigrant Wage Gap in Germany - Stephan L. Thomsen; Johannes Gernandt; Alisher Aldashev (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Immigrants consist of foreigners and citizens with migration background. We analyze the wage gap between natives and these two groups in Germany. The estimates show a substantial gap for both groups with respect to natives. Discarding immigrants who completed education abroad reduces much of the immigrants' wage gap. This implies educational attainment in Germany is an important component of economic integration and degrees obtained abroad are valued less.
Keywords: J61; J31; J15; 330; Immigration; wage gap; decomposition; Germany; Migranten; Lohndifferenzierung; Bildungsabschluss; Soziale Integration; Deutschland